2014
DOI: 10.1038/srep06990
|View full text |Cite
|
Sign up to set email alerts
|

Distinct composition of the oral indigenous microbiota in South Korean and Japanese adults

Abstract: A comparison of national surveys on oral health suggested that the population of South Korea has a better periodontal health status than that of Japan, despite their similar inherent backgrounds. Here, we investigated differences in oral bacterial assemblages between individuals from those two countries. To exclude potential effects of oral health condition on the microbiota, we selected 52 Korean and 88 Japanese orally healthy adults (aged 40–79 years) from the participants of two cohort studies, the Yangpyeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 29 publications
(38 reference statements)
4
44
0
Order By: Relevance
“…In fact, many reviewers of our report raised criticism about why we evaluated the microbiome of saliva but not that of subgingival plaque. Subsequently, we confirmed the association between the saliva microbiome and periodontal health in a comparison of Japanese and Korean populations (19). National surveys of dental health in Japan and Korea revealed that periodontal health was better in Korea, even though socioenvironmental factors related to periodontal health (e.g., oral hygiene behavior, smoking habit, number of dentists per capita, and coverage of dental therapy by public health insurance) were more favorable in Japan.…”
Section: The Salivary Microbiome and Its Relationship With Periodontasupporting
confidence: 69%
“…In fact, many reviewers of our report raised criticism about why we evaluated the microbiome of saliva but not that of subgingival plaque. Subsequently, we confirmed the association between the saliva microbiome and periodontal health in a comparison of Japanese and Korean populations (19). National surveys of dental health in Japan and Korea revealed that periodontal health was better in Korea, even though socioenvironmental factors related to periodontal health (e.g., oral hygiene behavior, smoking habit, number of dentists per capita, and coverage of dental therapy by public health insurance) were more favorable in Japan.…”
Section: The Salivary Microbiome and Its Relationship With Periodontasupporting
confidence: 69%
“…Oral microbiome studies in the Asia‐Pacific region have uncovered additional ethnogeographic differences among Japanese and Koreans that were correlated with susceptibility to periodontitis . Furthermore, metagenomic analysis of Chinese subjects provided a clear demonstration of the influence of plaque microbiota on gingival inflammation .…”
Section: The Asia‐pacific Region and The Microbiomementioning
confidence: 99%
“…59,61 Oral microbiome studies in the Asia-Pacific region have uncovered additional ethnogeographic differences among Japanese and Koreans that were correlated with susceptibility to periodontitis. 62 Furthermore, metagenomic analysis of Chinese subjects provided a clear demonstration of the influence of plaque microbiota on gingival inflammation. 46 Intriguingly, oral, salivary and gut microbiomes of Chinese patients suffering from rheumatoid arthritis-an autoimmune condition with respiratory manifestations-were significantly altered compared to controls.…”
Section: Respiratory Disease and The Microbiomementioning
confidence: 99%
“…There were a number of distinctive differences observed in the salivary microbiome between humans and marmosets. Previous studies reported clear differences among populations living under different geographical conditions [15, 16]. The differences were reportedly attributed mainly to differences in lifestyles, dietary habits, as well as sanitary and socioeconomic factors [17, 18].…”
Section: Discussionmentioning
confidence: 99%